Participação ocupacional de crianças com doença renal crônica em tratamento hemodialítico no estado do Pará - Corrêa, Iasmim Teles (Universidade Federal de São Carlos, 2026)
Chronic kidney disease is included among the complex chronic health conditions, affecting the vital functions of the kidneys and, in its most advanced stages, requiring renal replacement therapy, such as hemodialysis. Faced with the experience produced by the illness, numerous changes can occur in the patient and their families, in the physical body, and in the adaptation of routines and occupations. Therefore, the general objective of this study was to understand the participation in occupations of children with chronic kidney disease undergoing hemodialysis treatment. This is a qualitative study, of the descriptive, exploratory, and field research type. Seven children and seven mothers responsible for the care of the children assisted at the Pediatric Renal Replacement Therapy Center of the Santa Casa de Misericórdia do Pará Foundation participated in the research. The research was conducted using an interview guide directed at the children's caregivers and with the use of a playful resource, specifically a board game created for this research, to guide the conversation with the children and assist in data collection. The data were analyzed using the Content Analysis technique, with the aid of the MAXQDA® software. The results are presented in six categories entitled: “The discovery: The journey to hemodialysis treatment”, which refers to the different ways of discovering kidney disease and entering renal replacement therapy with hemodialysis; “The children's routine: Before and after hemodialysis treatment”, which presents the changes in the children's routine, that is, before and after starting hemodialysis treatment based on the mothers' reports; “The change: Occupational participation from the caregivers' perspective”, presenting the changes in the way daily occupations are performed after the start of hemodialysis treatment; “Occupational participation from the children's perspective”, presents the way in which occupations are performed and participated in according to the children's narrative; “Difficulty in participating in occupations”, exposing the accounts of caregivers and children about the most difficult occupations to perform while undergoing hemodialysis treatment; Finally, the section "Significant Occupations" also presents the accounts of the children and their caregivers regarding the most important occupations for children undergoing hemodialysis treatment. The results showed that children with chronic kidney disease undergoing hemodialysis treatment experience a significant impact on occupational participation in various occupational categories, mainly ADLs (Activities of Daily Living), Play, Leisure, Education, and Sleep and Rest. Therefore, they experience the development of occupational adaptations that allow them to perform daily activities, in addition to experiencing significant occupational deprivations as a consequence of their condition, which can influence their health and well-being. This study reinforces the need for interventions that consider the specific needs of children and promote opportunities for full occupational participation, minimizing the effects of occupational deprivation and improving the care offered to children with chronic kidney disease undergoing hemodialysis, strengthening child-centered practices, and reinforcing the importance of occupational participation for the quality of life of this population.
Occupational participation of children with chronic kidney disease undergoing hemodialysis treatment in the state of Pará
Keywords: Criança; Doença renal crônica; Hemodiálise; Ocupações; Terapia ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar